Erasmo e Lutero: distintas concepções de livre-arbítrio - Nascimento, Sidnei Francisco do (2006)
The thesis presents the confrontation of ideas related to free will concept between Erasmus and Martin Luther in the Christian Humanism and Protestant Reform context. By on eh and, Erasmus admits the free will as a utilization of human will, in which, the human being can help for his own eternal salvation, or refuse it forever. To admit the possibility of human will get closer or to be along way off God, the Christian Humanist take in consideration the philosophies from late ancient times, for ins stance, the Platonic, the Stoicism and the Early Patristic. By other hand, the Luther s Theology breaks off with the Christian it y ratified by many authorities and councils, and it declares that the human nature, decayed and sinner, only can get the eternal salvation through suffering. According to the Reformer, the human will, perverted by original's in, just go es towards the evil